Application of Mycorrhizae and Beauveria in Organic Farming System Effectively Control Leafminers and Enhance Shallot Production - Shahabuddin Saleh; Alam Anshary; Usman Made; Mahfudz Mahfudz; Muhammad Basir-Cyio (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
An increasing studies related with the detrimental effects of agrochemicals suggested the advantage of biofertilizers and biopesticides uses to support the sustainable farming system. This study aimed to evaluate the response of shallot ‘Lembah Palu’ with the application of arbuscular mycorrhizae (AM) and Beauveria bassiana (Bb) under organic farming system. A split-plot experiment was designed to combine Bb at two intervals (every 5 and 10 days) and AM with three rates (0; 5; and 10 g per plant). Leafminer population and infestation, root colonization, root biomass, and shallot yield were observed. Application of the AM and Bb affected shallot production and leafminer infestation, independently. Mycorrhizae application increased the root biomass and yield of shallot but gave negligible effects on population and leafminer attack. The shallot production with no mycorrhizae was significantly lower compared to both mycorrhizae application rates of 5 g and 10 g. The application of B. bassiana every 5 days was more effective in suppressing the population and infestation of leafminers compared to that every 10 day-treatment. The study points out the positive contribution of the mycorrhizae and B. bassiana in the shallot cultivation and supports the implementation of the organic farming system.